Tolkāppiyam in English : translation, with the Tamil text, transliteration in the roman script, introduction, glossary, and illustrations - Murugan, V. (Vellayagounder); John Samuel, G.; Tolkāppiyar; Institute of Asian Studies (Madras, India) (Chennai : Institute of Asian Studies, 2000)
Prijevod stare tamilske gramatike
Bibliografija: str. [683]-687.
Engleski i tamilski
Keywords: indijski jezici -- dravidski jezici -- tamilski jezik - gramatika; tamilska književnost